Genetic Variability and Association Analysis Between Yield and Yield-related Traits in Greengram (Vigna radiata (L.) Wilczek) - Mokshith, Venkata Raja V.; Roja, V.; Satyanarayana, N. Hari; Jayalalitha, K.; Supriya, P. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during rabi season (November, 2023–February, 2024) at the Regional Agricultural Research Station (RARS), Lam, Guntur, Andhra Pradesh, India to study the genetic variability, heritability, genetic advance, and correlations between plant yield and quantitative traits by evaluating eighty-three greengram genotypes following an augmented complete randomized block design. All studied traits showed significant variability through the analysis of variance (ANOVA) and most of the traits showed a near-normal distribution in their mean phenotypic distribution. The study found that the pods plant-1 exhibited the highest variability, while test weight and seeds pod-1 showed the least variability. Pods plant-1 displayed a high range of values for genetic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV). In contrast, low GCV and PCV values were observed for the trait’s days to 50% flowering and days to maturity. Heritability ranged from 74.23% for seeds pod-1 to 99.72% for pods plant-1. Broad sense heritability estimates and GAM were high for all the characteristics, except for the trait days to maturity. This suggested the predominant influence of additive gene action on these traits, making them suitable for selection-based improvements. Through correlation studies, the traits clusters plant-1, pods plant-1, and seeds pod-1 obtained a strong significant positive association with seed yield plant-1. These traits are effective for direct selection in crop improvement. Overall, yield and yield-attributing traits exhibited significant variations and high heritability, indicating their potential for enhancing greengram.